Ecologia térmica de anuros da Caatinga, Nordeste do Brasil - Carvalho Ferreira, Larissa (2023)
Thermal ecology of anurans in the Caatinga, Northeastern Brazil. Anurans regulate their body temperature through external heat sources. In this sense, the microhabitat used can influence this physiological process. Thus, the objective of this study was to verify the body temperature of anuran species in the Caatinga domain and to correlate the possible variations to the different microhabitats used. For this, active searches were carried out during the day and night shifts, between August 2019 and May 2021. The frogs were captured manually to measure the cloacal temperature and then released. Substrate and air temperatures were also checked for associations with body temperature. In total, 420 frogs were captured, and the body temperature was obtained from 147 individuals of five species in the rainy season (Leptodactylus macrosternum, Scinax x-signatus, Rhinella granulosa, Rhinella diptycha and Pithecopus gonzagai), and from 273 individuals of four species in the dry season (L. macrosternum, S. x-signatus, R. granulosa and R. diptycha). In general, the highest body temperature averages (28.4-29.3ºC) were observed in the rainy season for L. macrosternum, R. granulosa and R. diptycha. The most preferred microhabitats of anurans were soil and water. Finally, even though an association between body temperature and air temperature was found, substrate temperature proved to be the most important source of thermal regulation for most anuran species investigated.